2012
DOI: 10.1016/j.triboint.2011.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of grease rheology on thrust ball bearings friction torque

Abstract: a b s t r a c tThe friction torque and the operating temperatures in a thrust ball bearing were measured for seven different types of greases, including three biodegradable greases having low toxicity. These friction torque tests were performed using a modified Four-Ball machine.Rheological evaluations of the lubricating greases were made using a rheometer. Bleed oils were extracted from the greases and the dynamic viscosities were measured.In order to compare the performance of the lubricant greases in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 10 publications
3
32
0
Order By: Relevance
“…Vergne et al [14,15] also found similar film thickness values between lithium mineral greases and their bleed oils. This observation is also in close agreement with the latest findings of the authors [22], where the predictions of the rolling bearing friction torque had better agreement with the corresponding measurements when bleed oil properties were used instead of base oil properties. Figs.…”
Section: Film Thickness Measurementssupporting
confidence: 92%
“…Vergne et al [14,15] also found similar film thickness values between lithium mineral greases and their bleed oils. This observation is also in close agreement with the latest findings of the authors [22], where the predictions of the rolling bearing friction torque had better agreement with the corresponding measurements when bleed oil properties were used instead of base oil properties. Figs.…”
Section: Film Thickness Measurementssupporting
confidence: 92%
“…A similar trend was previously observed by the authors with commercial greases of the same basic lithium thickener-ester oil composition [19]. Various characteristics of ester-based greases have been proposed in literature as negatively affecting their lubrication behaviour [38,39], with increased propensity for contact starvation suggested as perhaps the most significant factor [40]. However, in the current study the onset of starvation can be excluded, as the tests were performed in fully flooded conditions by directing the supply of grease to the contact by means of a grease scoop.…”
Section: Effect Of Base Oil Typesupporting
confidence: 87%
“…9. Literature [40][41][42] suggests that shorter lithium thickener fibres can produce thinner films at low speeds, and consequently higher friction due to increased asperity contacts [43]. Kanazawa et al [22] suggest that the 'transition film thickness' for a given grease, and hence the extent of the region where thickener film enhancement is evident, is determined by the ratio of thickener fibre size to the film thickness obtained by the base oil alone, i.e.…”
Section: Effect Of Base Oil Typementioning
confidence: 99%
“…Cousseau et al investigated the influence of grease rheological parameter for thrust bearing torques and proposed that the bearing rolling torque is dependent on the viscosity of the bleed oil [1]. Oikawa et al indicated a relationship between yield stress of greases and ball bearing torque and that higher yield stress of grease leads to channeling state in a bearing, which is effective in torque reduction [2].…”
Section: Introductionmentioning
confidence: 99%